2018
DOI: 10.3892/ol.2018.8797
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of long non‑coding RNA GAS5 promotes cell proliferation, migration and invasion in esophageal squamous cell carcinoma

Abstract: The present study aimed to investigate the potential role of long non-coding RNA growth arrest-specific transcript 5 (lncRNA GAS5) in the progression of esophageal squamous cell carcinoma (ESCC) and to reveal its possible regulatory mechanism. The expression of lncRNA GAS5 in ESCC tissues and cell lines was analyzed using reverse transcription-quantitative polymerase chain reaction and western blot analysis. The overexpression vector pc-GAS5 and control vector pc-negative control (NC), containing no GAS5 seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
(35 reference statements)
3
13
0
Order By: Relevance
“…However, Ke et al insisted that GAS5 was an anticancer gene in esophageal tumor. Overexpression of GAS5 significantly impeded tumorigenesis via EMT . Huang et al verified the influences of GAS5 on proliferation, invasion and migration, which was consistent with Ke K's opinions .…”
Section: Biological Functions and Mechanisms Of Snhgs In Digestive Camentioning
confidence: 53%
“…However, Ke et al insisted that GAS5 was an anticancer gene in esophageal tumor. Overexpression of GAS5 significantly impeded tumorigenesis via EMT . Huang et al verified the influences of GAS5 on proliferation, invasion and migration, which was consistent with Ke K's opinions .…”
Section: Biological Functions and Mechanisms Of Snhgs In Digestive Camentioning
confidence: 53%
“…23 Another study also found that GAS5 was downregulated in ESCC tissues and EC cells. 60 More studies exploring the contribution of GAS5 in the pathogenesis of ESCC and its complications should be encouraged. Gastric cancer (GC) is one of the most common malignant diseases in the world.…”
Section: Clinical Relevancementioning
confidence: 99%
“…23 Likewise, GAS5 significantly inhibited cell proliferation and invasion, and induced cell cycle arrest by activating the ATM-p-checkpoint kinase 2 (CHK2) pathways and regulating EMT-associated proteins. 60 The feedback loop between GAS5 and interferon (INF) signaling via the janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway played an important anti-tumor role of GAS5 in ESCC cells. 127 These findings contribute to our understanding of the mechanisms of miRNA-lncRNA interaction and may provide insight for new avenues in diagnosis and treatment of ESCC.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Long non-coding RNAs have been discovered to be special molecular regulators in ESCC. Previous studies have shown that overexpression of lncRNA GAS5 would result in cell cycle arrest at the G2/M stage by regulating the ATM-CHK2 pathway to inhibit cell proliferation, migration, and invasion in ESCC [ 45 ]. Similarly, a study has found that positive expression of LncRNA FER1L4 inhibits cell proliferation, invasion, promotes apoptosis and increases the cell cycle distribution in G0/G1 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%